The Role Of Audit Committees In The Financial Performance Of Companies An Empirical Study On Banks Listed On The Damascus Securities Exchange (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to study the relationship between the role of audit committees and the financial performance of companies. Especially the banks operating in the Damascus Stock Exchange, and for that, the researcher collected data on the independent variable represented in the formation of the audit committee from the governance reports published on the website of the Syrian Securities and Markets Authority, as well as data on the dependent variable represented by financial performance, through financial statements and reports For banks listed on the Damascus Securities Exchange, and the Syrian Securities and Markets Authority. The 14 banks listed on the Damascus Securities Exchange and the Syrian Securities and Markets Authority during the period from 2009 to 2017, the data was studied through the Eviews10 program. The study reached a set of results, the most important of which are:There is a negative relationship between each of the independence variables, the number of audit committee meetings with the external auditor, and the rate of return on assets, and this relationship is not statistically significant. There is also a positive relationship between the variables of financial and accounting expertise in audit committees and the number of committee meetings annually with the rate of return on assets, but Not statistically significant.